2021
DOI: 10.1039/d1tc01513c
|View full text |Cite
|
Sign up to set email alerts
|

A high-temperature quantum anomalous Hall effect in electride gadolinium monohalides

Abstract: Electrides, with interstitial electrons loosely trapped in lattice voids behaving as anions, are favorable for achieving band inversions required for topological phases. In this paper, we predict that the quantum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The contribution of Cl and Br atoms to the total magnetic moment is very small and negligible. Our calculated in-plane lattice constants of FM monolayers GdCl and GdBr are 3.70 and 3.78 Å, respectively, agreeing well with the previous result …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The contribution of Cl and Br atoms to the total magnetic moment is very small and negligible. Our calculated in-plane lattice constants of FM monolayers GdCl and GdBr are 3.70 and 3.78 Å, respectively, agreeing well with the previous result …”
Section: Resultssupporting
confidence: 92%
“…Our calculated in-plane lattice constants of FM monolayers GdCl and GdBr are 3.70 and 3.78 Å, respectively, agreeing well with the previous result. 35 As shown in Figure S3a,c, there are no imaginary phonon modes in the whole Brillouin zone of FM monolayers GdCl and GdBr except for the negligible imaginary frequencies around the Γ-point. Due to the lattice instability of the long-wave undulations, 45 the imaginary phonon modes at the Γ-point were reported in other 2D materials which are dynamically stable.…”
Section: Structure and Stability Of The Gdx (X = CL And Br)mentioning
confidence: 89%
See 1 more Smart Citation
“…These cones give rise to appealing physical properties, e.g., high carrier mobility 16 and quantum anomalous Hall effect. [17][18][19][20] Formally, topological insulators are typically characterized by an odd value of the Z 2 topological invariant. 1,2,21,22 Previous work has shown that the time-reversal invariant band in three dimensions is characterized by four Z 2 invariants, resulting in 16 types of topological insulators.…”
Section: Introductionmentioning
confidence: 99%